2006
DOI: 10.1111/j.1572-0241.2006.00686.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of NSAID-Associated Gastrointestinal Lesions: A Comparison Study PantoprazoleversusOmeprazole

Abstract: For patients taking NSAIDs continually, pantoprazole 20 mg o.d., pantoprazole 40 mg o.d., or omeprazole 20 mg o.d. provide equivalent, effective, and well-tolerated prophylaxis against GI lesions, including peptic ulcers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
2
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 28 publications
1
40
2
2
Order By: Relevance
“…Approximately 30 million patients consume NSAIDs on a daily basis (1). However, NSAIDs have limitations; they induces gastropathy, and ϳ107,000 patients are hospitalized every year due to NSAIDrelated gastrointestinal complications (3).…”
Section: Nsaidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 30 million patients consume NSAIDs on a daily basis (1). However, NSAIDs have limitations; they induces gastropathy, and ϳ107,000 patients are hospitalized every year due to NSAIDrelated gastrointestinal complications (3).…”
Section: Nsaidsmentioning
confidence: 99%
“…2 are the most popular drugs commonly used throughout the world for the treatment of pain, inflammation, rheumatic disorders, and osteoarthritis (1,2). Approximately 30 million patients consume NSAIDs on a daily basis (1).…”
Section: Nsaidsmentioning
confidence: 99%
“…Non-steroidal anti-inflammatory drugs (NSAIDs), 2 commonly used for the treatment of arthritis and other musculoskeletal disorders are considered to be one of the most important causative factors for gastric damage (1)(2)(3). Although various mechanisms have been suggested for NSAID-induced gastric ulcer (4 -7), recent studies suggest that increased apoptotic cell death and simultaneous block of mucosal cell renewal play major roles in the development of mucosal lesion (8 -10).…”
mentioning
confidence: 99%
“…The authors concluded that both doses of pantoprazole and omeprazole provide equivalent, effective, and well-tolerated primary prophylaxis against the endoscopic development of peptic ulcer disease in chronic NSAID users. 38 While most COX-2 inhibitors are no longer widely available due to safety concerns, these drugs provided an alternative strategy in primary and secondary prophylaxis of gastrointestinal complications related to chronic NSAIDs. Several large outcomes studies have demonstrated signifi cantly fewer clinically important upper gastrointestinal events in patients treated with selective COX-2 inhibitors compared to non-selective NSAIDs.…”
Section: Primary Prophylaxis Of Nsaid-induced Peptic Ulcer Diseasementioning
confidence: 99%